Brand Equity Analysis of Formula Milk for Age 1-3 Years Old at Integrated Healthcare Center Mawar IX Bandung - Nurifda, Khairunnisa Salma; Firman, Achmad; Fitriani, Anita (Jurnal Peternakan, 2024)
This study aims to describe the characteristics of consumers in purchasing formula milk products aged 1-3 years and to analyze the brand equity of formula milk aged 1-3 years at Integrated Healthcare Center Mawar IX, RW 9, Cipamokolan Village, Rancasari District, Bandung City. The method used mixed research methods and sample taking used a purposive sampling technique. Based on observations, there were 51 people who suit the criteria. Data were analyzed using descriptive analysis, Cochran test, brand switching pattern matrix, and estimation of market share. Based on research, the characteristics of its consumers are dominated by housewives aged 19-34 years with undergraduate/postgraduate graduates who have children aged 12-23 months with an income of IDR 500,000-5,000,000 and expenditures of IDR 100,000-3,000,000 per month regarding knowledge of child nutrition and obtaining information regarding formula milk from advertisements so that they buy formula milk with a frequency of 1-2 times/month and a small product volume. The results show that Dancow Batita and SGM have a fairly strong brand equity value where these two brands have a brand image with 11 brand associations and a good quality perception. SGM outperformed brand awareness and estimated market share, while Dancow Batita led in brand loyalty. While both brands are equally superior for brand association and perceived quality.